Analytical Method to Improve the Security of Internet of Things with Limited Resources - Abdul Khan; Shahan Siddiqui; Muhammad Irshad; Saif Ali; Muhammad Saleem; Shahid Iqbal (EAI Endorsed Transactions on Internet of Things, 2019)
This research is about the information security of very obliged gadgets. Design Science Research (DSR) Method is utilizedfor this reason. It let us pick up the fundamental thought and exploration of the primary issue space. This is a procedure ofcombining distinctive pre-affirmed examines to pick up the goal. Symmetric cryptography will be utilized as a noteworthydevice in various information items and entryway gadgets. The principle target of this exploration is to give security toexceptionally constrained gadgets as they are not ready to convey utilizing TLS or DTLS given a deficiency of assets. Thisarrangement is a finished bundle to give credibility, information honesty and privacy, either information is making a trip toentryway, gadgets or the web. At the information interface layer, AES symmetric encryption is utilized and informationquestions likewise are encoded utilizing a similar encryption strategy. Assessment is performed using wire shark.